Internal idea contests: Work environment perceptions and the moderating role of power distance - Bjoern Hober; Mario Schaarschmidt; Harald F. O. von Korflesch (Journal of Innovation & Knowledge (JIK), 2021)
Internal innovation contests are the most frequently realized practical approach to capturing organization-wide creativity. Here, important business challenges are digitally broadcasted to a large group of potential volunteers within the firm regardless of their position. Innovation theory highlights that positive perceptions of individuals' work environment positively influence their innovating behaviors, while negative perceptions suppress them. We surveyed employees of a specific subsidiary of a large German company in the telecommunications industry that is responsible for the management of the group's entire product portfolio. The results indicated that (1) not all elements of the work environment influence employees' intrinsic motivation to participate and (2) power distance orientation matters when intrinsic motivation leads to willingness to participate in future internal idea contests.
Keywords: 650; Creativity theory; Internal idea contests; Power distance